Comparative assessment of corrosion of concrete reinforced with unprotected steel and hot-dip galvanized steel (2017)
Increasing the lifespan of structures is of great importance for civil construction, either because of economic aspects or security to the users. Corrosion of reinforcement is one of the most recurring problems, especially in environments with high chloride content. One of the most effective alternatives to protect reinforcement against corrosion is the hot-dip galvanizing of steel bars, with the addition of a zinc coating that is consumed before steel entering in reaction. In this paper, it was investigated the comparison between unprotected steel bars and hot-dip galvanized ones, immersed in four types of concrete with different water/cement ratio, and subjected to accelerated corrosion test executed by the CAIM procedure. It was observed corrosion decreased for all types of concrete, reaching 70.5% of reduction for the richest mixture, showing that the hot-dip galvanizing may be an important alternative to the wired concrete structures, particularly when used in combination with mixtures of greater durability.